Overcoming the Aporia of Modernity – A Proposal from Latin America (KULT_online, 2013)
With a title that translates as "The Counter Discourse of Modernity", this work by the Argentinean and Mexican philosopher Enrique Dussel can be interpreted as an attempt to reintroduce Latin America into the history of philosophy. According to Dussel, the philosophical discourse about the modern age begins with the debate concerning the right to colonize. The eurocentric character of modernity could be dispelled by an intercultural dialogue, beginning with a South-South-cooperation. The book opens up a thought-provoking and worthwhile reading for a Latin American perspective on modernity.